WHAT SCHOOL INSTITUTION CAN LEARN FROM MULTI-PLAYER ONLINE GAMES DEVELOPMENT AND IT CHALLENGE FOR PUPILS - Sampoerno, Mohd. Norma; Saadah, Mar Atun (LPPM Universitas PGRI Silampari Lubuklinggau, 2024)
This study analyzes verbal violence against female adolescents playing multiplayer online games in Jambi City from a sociolinguistic perspective. Communication features in multiplayer online games often involve verbal violence, especially against female players who are considered to have less playing skills than male players. This study uses qualitative data obtained through interviews and FGDs, which were analyzed using NVIVO. This study shows that patronizing and criticizing behavior is common among FF players. Verbal violence results in changes in player behavior. Currently, the Jambi City Government does not have a specific instrument to address the problem of verbal violence among adolescents, especially those aged 10 to 14 years.